'Mindful eating' for reducing emotional eating in patients with overweight or obesity in primary care settings: A randomized controlled trial. (17th November 2022) - Morillo‐Sarto, Héctor; López‐del‐Hoyo, Yolanda; Pérez‐Aranda, Adrián; Modrego‐Alarcón, Marta; Barceló‐Soler, Alberto; Borao, Luis; Puebla‐Guedea, Marta; Demarzo, Marcelo; García‐Campayo, Javier; Montero‐Marin, Jesús
Abstract: Objective: The primary aim of this study was to analyse the efficacy of a 'mindful eating' programme for reducing emotional eating in patients with overweight or obesity. Method: A cluster randomized controlled trial (reg. NCT03927534) was conducted with 76 participants with overweight/obesity who were assigned to 'mindful eating' (7 weeks) + treatment as usual (TAU), or to TAU alone. They were assessed at baseline, posttreatment and 12‐month follow‐up. The main outcome was 'emotional eating' (Dutch Eating Behaviour Questionnaire, DEBQ); other eating behaviours were also assessed along with psychological and physiological variables. Results: 'Mindful eating' + TAU reduced emotional eating both at posttreatment ( B  = −0.27; p  = 0.006; d  = 0.35) and follow‐up ( B  = −0.53; p  < 0.001; d  = 0.69) compared to the control group (TAU alone). 'External eating' (DEBQ) was also significantly improved by the intervention at both timepoints. Significant effects at follow‐up were observed for some secondary outcomes related to bulimic behaviours, mindful eating, mindfulness, and self‐compassion. Weight and other physiological parameters were not significantly affected by 'mindful eating' + TAU. Conclusions: These findings support the efficacy of the 'mindful eating' + TAU programme for reducing emotional and external eating, along with some other secondary measures, but no significant changes in weight reduction were observed. Highlights: 'Mindful eating' added to treatment as usual (TAU) is more effective than TAU alone for reducing the emotional eating pattern of obese and overweight patients in primary care (PC) settings. The programme produced improvements in secondary outcomes such as external eating, the severity of bulimic symptoms, the frequency of binge episodes, and some mindfulness and self‐compassion facets. The body mass index (BMI) and other physiological variables were not significantly reduced by the 'Mindful eating' programme; future studies should try to overcome some methodological shortcomings of the present study.